2023
DOI: 10.18203/2320-6012.ijrms20231037
|View full text |Cite
|
Sign up to set email alerts
|

A real-world evidence study to evaluate the efficacy of software-driven digital therapeutics on major adverse cardiovascular events, vitals, adherence to medication and lifestyle changes among patients with coronary artery disease or post-coronary interventions

Abstract: Background: Coronary artery disease (CAD), a leading cause of cardiovascular disease (CVD) mortality worldwide, is a major health concern in India due to the high rates of the disease. Acute coronary syndrome (ACS) is a prevalent form of CAD that requires prompt treatment. Digital therapeutics (DTx) is an emerging field that employs remote monitoring and behavioural changes to manage diseases, with promising outcomes in ACS and post-percutaneous coronary intervention (PCI) patients. This study evaluates the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the recent pilot study conducted on Indian patients with CAD (n=30), the efficacy of the DTx for HF was assessed over a three-month follow-up. Overall observations indicated that the use of DTx improved medication adherence and blood pressure control in patients with acute coronary syndrome (ACS) and/or post-percutaneous coronary intervention (PCI) [35].…”
Section: Relevant Research Studies and Clinical Trialsmentioning
confidence: 99%
“…In the recent pilot study conducted on Indian patients with CAD (n=30), the efficacy of the DTx for HF was assessed over a three-month follow-up. Overall observations indicated that the use of DTx improved medication adherence and blood pressure control in patients with acute coronary syndrome (ACS) and/or post-percutaneous coronary intervention (PCI) [35].…”
Section: Relevant Research Studies and Clinical Trialsmentioning
confidence: 99%